THE ADOPTION OF ENGLISH MEDIUM INSTRUCTION (EMI) IN ALGERIAN HIGHER EDUCATION: LINGUISTIC AND IDENTITY CONSIDERATIONS - Toufaha SAHKI (Ziglôbitha)
Abstract : This study investigates the implementation of English Medium Instruction (EMI) in Algerian higher education, focusing on its impact on academic attainment, the preservation of local languages, local identity, and the challenges faced by educators. With globalization and internationalization as primary drivers, EMI has seen a significant prevalence globally, offering students opportunities to improve language proficiency and gain access to global knowledge. However, concerns have emerged regarding the possible erosion of local languages, the influence of EMI on cultural identity, and the challenges in effectively implementing such a system in non-native English contexts. Using qualitative interviews with 15 university teachers from various disciplines, this research examines their perspectives on these issues and identifies key challenges in the process. The findings reveal mixed opinions: while EMI enhances students' language skills and employability, it poses significant challenges to academic performance, particularly in specialized fields that require technical vocabulary. Teachers also expressed concerns about the marginalization of Arabic and French, the two predominant languages in Algeria, and the potential loss of local cultural identity. Additionally, faculty training, language proficiency, and resource limitations emerged as critical obstacles in implementing EMI effectively. The study suggests that a balanced approach is needed, one that integrates English as a global medium while preserving the cultural and linguistic heritage of Algeria. It recommends comprehensive teacher training, improved language support programs, and institutional commitment to bilingual education to ensure the successful adoption of EMI.